The EFL Learners’ Reading Anxiety Level at English Department UNP - Insan Kamil; Fitrawati Fitrawati (Journal of English Language Teaching, 2023)
This research aims to investigate the levels of foreign language reading anxiety and to determine the dominant factors that cause the foreign language reading anxiety of the academic year 2019 English education students at Universitas Negeri Padang. Thirty students were involved in this research. The data were collected through two questionnaires. The first questionnaire is the Foreign Language Reading Anxiety Scales (FLRAS) to investigate the level of reading anxiety. The second questionnaire is a developed questionnaire to determine the dominant factor of foreign language reading anxiety. The first finding revealed that more than half of the students had a medium anxiety level (67%). 20% fell into a high level of anxiety, and 13% of the students fell into a low level of anxiety. Two aspects of foreign language reading anxiety are the text feature and personal factors. In the aspect of text feature factor, there are three themes: unknown vocabulary (71, 17% agreed), unfamiliar topic (66, 04% agreed) and unfamiliar culture (58, 17% agreed). On the personal factor aspect, there are two themes: worry about reading effect (67, 36% agreed) and fear of making errors (64% agreed). The second finding revealed that unknown vocabulary ranked first as the factor of reading anxiety, followed by the worry about reading effect in second place, the unfamiliar topics in third place, the fear of making errors in fourth place, and the unfamiliar culture in the fifth place.